2021
DOI: 10.3390/cells10030582
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an Agave Phosphoenolpyruvate Carboxylase Improves Plant Growth and Stress Tolerance

Abstract: It has been challenging to simultaneously improve photosynthesis and stress tolerance in plants. Crassulacean acid metabolism (CAM) is a CO2-concentrating mechanism that facilitates plant adaptation to water-limited environments. We hypothesized that the ectopic expression of a CAM-specific phosphoenolpyruvate carboxylase (PEPC), an enzyme that catalyzes primary CO2 fixation in CAM plants, would enhance both photosynthesis and abiotic stress tolerance. To test this hypothesis, we engineered a CAM-specific PEPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 80 publications
0
17
0
1
Order By: Relevance
“…Evidence of a tight interconnection between the circadian oscillator and dark CO 2 fixation is also shown by the observation that suppression of PEPC expression by RNA interference results in altered expression of certain core circadian clock genes (Boxall et al ., 2020 ). On the other hand, overexpression of the CAM isoform of PEPC in a C 3 background ( Arabidopsis or tobacco), while leading to increased malate content and daytime accumulation, does not itself result in a switch to night‐time acidification (Lim et al ., 2019 ; Liu et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of a tight interconnection between the circadian oscillator and dark CO 2 fixation is also shown by the observation that suppression of PEPC expression by RNA interference results in altered expression of certain core circadian clock genes (Boxall et al ., 2020 ). On the other hand, overexpression of the CAM isoform of PEPC in a C 3 background ( Arabidopsis or tobacco), while leading to increased malate content and daytime accumulation, does not itself result in a switch to night‐time acidification (Lim et al ., 2019 ; Liu et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2021) [ 42 ] demonstrated that the overexpression of PEPc activity significantly increases salt tolerance in transgenic tobacco plants. In general, this enhancement is related to proline production, which plays an important role in protecting membrane integrity, photosynthesis, regulating osmotic balance, and activating the ROS scavenging system.…”
Section: Resultsmentioning
confidence: 99%
“…shown in agave, where a single gene encoding a phosphoenolpyruvate carboxylase enhances the plant's climate resilience (Liu et al, 2021). Not only the gain of genes, but also the loss of genes has been associated with adaptive traits, such as the evolution of particular diets in bats (Blumer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While environmental adaptations are commonly highly polygenic (Barghi et al, 2019; Hartke et al, 2021; Pfenninger et al, 2021; Rivas et al, 2018), there is increasing evidence of the effect of single gene content variation (Liu et al, 2021). For example, as has been recently shown in agave, where a single gene encoding a phosphoenolpyruvate carboxylase enhances the plant’s climate resilience (Liu et al, 2021). Not only the gain of genes, but also the loss of genes has been associated with adaptive traits, such as the evolution of particular diets in bats (Blumer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%